Threatened identity and chalenges of the national revival of the Serbs in the Kingdom of Yugoslavia - Marković, Saša (Sociološki pregled, 2023)
The Yugoslav experience of the Serbian national idea in the mid-1930s was seriously undermined. The assassination of King Aleksandar Karađorđević was an event that, after the rebellious response of loyalty, irreversibly initiated the search for the revival of the national idea and its racing modern European models. Since the international geopolitical situation witnessed the process of the failure of the Peace Treaty of Versailles, new national positioning occupied the attention of the Serbian intellectual elite. This paper presents the development of the ideas of national revival through combining formerly valid standpoints which, on the one hand, encourage the development of the collectivist type of society and, on the other hand, the redefinition of the individual approach in the existing standpoint about democracy. Their contradicting views affected pluralism, but there was also a threat of exclusive reflexions being transformed into antagonism.
Keywords: Serbs; revival; nation; democracy; society; collectivism